RENEWABLE ENERGY EDUCATION-BASED HUMAN RESOURCE DEVELOPMENT MODEL FOR THE CONSERVATION OF THE PULAU KETAM FOREST RESERVE THROUGH COLLABORATIVE CSR OF UNPAB–PTSS MALAYSIA - Sri Rahayu; Elfitra Desy Surya; Rosasmanizan Binti Ahmad; Faisal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study develops a human resource development (HRD) model based on renewable energy education to strengthen the conservation of the Pulau Ketam Forest Reserve through a collaborative Corporate Social Responsibility (CSR) initiative between Universitas Pembangunan Panca Budi (UNPAB), Indonesia, and Politeknik Tuanku Syed Sirajuddin (PTSS), Malaysia. Using a qualitative approach with Participatory Action Research (PAR), the study examines how renewable energy education contributes to community empowerment, forest preservation, and sustainable livelihoods. Data were collected through interviews, surveys, and focus group discussions involving local communities, NGOs, and academic stakeholders. The findings reveal that renewable energy education significantly enhances technical skills, environmental awareness, and social resilience while creating opportunities for sustainable economic activities. The proposed HRD model emphasizes capacity building, cross-border CSR collaboration, and community participation in conservation. This research contributes to the literature on sustainable HRM, CSR practices in ASEAN, and the role of renewable energy education in ecological preservation.